A color channel multiplexing approach for robust discrete wavelet transform based image watermarking. (5th August 2022) - Saritas, Omer Faruk; Ozturk, Serkan
Summary: Copyright protection of digital images has become a consequential issue in recent years. To prevent a breach of copyright for a color image, this article presents a novel discrete wavelet transform (DWT) based robust image watermarking method with a color channel multiplexing approach. In this proposed method, the original color image is separated into red, green, and blue color channels. One of these color channels is copied and a set of four channels is obtained. Then these channels are combined to obtain a new gray‐level cover image. 2‐level DWT is performed on the cover image. Arnold scrambled binary watermark image i embedded into the low‐frequency sub‐band of the cover image. 2‐level inverse DWT is performed to produce a gray‐level watermarked image. Then a demultiplexing process is performed by separating the gray‐level watermarked image into four color channels. The average values of the two copied color channels are calculated and then converted into a single‐color channel. Finally, the watermarked color image is get by merging three different color channels. To approve the performance of the presented method, various experimental tests have been performed and a benchmarking analysis has been conducted. The results show that the proposed method is robust against non‐linear and linear attacks while protecting watermarking imperceptibility.